Prevalence of alcohol-tolerant and antibiotic-resistant bacterial pathogens on public hand sanitizer dispensers. (September 2022) - Yeung, Y.W.S.; Ma, Y.; Liu, S.Y.; Pun, W.H.; Chua, S.L.
Summary: Background: Since the advent of the COVID-19 pandemic, alcohol-based hand sanitizer dispensers (HSDs) have been installed in most public and clinical settings for hygiene purposes and convenient application. Aim: To determine whether sanitizer-tolerant bacterial pathogens can colonize HSDs, spreading diseases and antibiotic resistance. Methods: Sampling was conducted from operational automatic HSDs, specifically the dispensing nozzle in direct contact with sanitizer. Culture-dependent cultivation of bacteria and MALDI-TOF were employed to assess microbiological contamination. Bacterial isolates were selected for rapid killing and biofilm eradication assays with alcohol treatment. Antibiotic minimum inhibitory concentration assays were performed according to the Clinical and Laboratory Standards Institute guidelines. Virulence potential of bacterial isolates was evaluated in the Caenorhadbitis elegans infection model. Findings: Nearly 50% of HSDs from 52 locations, including clinical settings, food industry, and public spaces, contain microbial contamination at 10 3 –10 6 bacteria/mL. Bacterial identification revealed Bacillus cereus as the most frequent pathogen (29%), while Enterobacter cloacae was the only Gram-negative bacterial pathogen (2%). Selecting B. cereus and E. cloacae isolates for further evaluation, these isolates and associated biofilms were found to be tolerant to alcohol with survival up to 70%. They possessed resistance to various antibiotic classes, with higher virulence than laboratory strains in the C. elegans infection model. Conclusion: HSDs serve as potential breeding grounds for dissemination of pathogens and antibiotic resistance across unaware users. Proper HSD maintenance will ensure protection of public health and sustainable use of sanitizing alcohols, to prevent emergence of alcohol-resistant pathogens.